Clinical and demographic profile of patients treated with electro convulsive therapy from a tertiary care psychiatry hospital in North India - Ismail, Haamid; Roub, Fazle; Kour, Sanjeet; Zargar, Waris Ahmad (International Journal of Research in Medical Sciences, 2020)
Background: Electro-convulsive therapy (ECT) refers to the electrical stimulation of the brain to produce seizures for therapeutic purpose. This study was undertaken with the aim of exploring the clinical and demographic profile of patients treated with ECT from a tertiary care psychiatry hospital in north India. Methods: It was a retrospective descriptive study of patients who were treated with ECT after admission in the inpatient psychiatry unit of Institute of mental health and neurosciences Kashmir during a period of one year (March 2017 to February 2018). Results: A total of 70 patients received ECT during the course of one year. About 72.85% of the patients belonged to 20-39 years age group. Female patients constituted more than half of the subjects (55.71%). Review of diagnostic profile showed that majority of patients receiving ECT were suffering from Schizophrenia (35.71%), followed by bipolar affective disorder (28.57%), depressive disorder (28.57%), schizoaffective disorder (4.28%) and substance induced mood/psychotic disorders (2.85%). A significant majority of subjects (57.13%) received about 7-9 ECT sessions. No any major complications were noted during ECT treatment. Conclusions: This study suggests that ECT, use as a treatment modality is common in adults between 20 to 39 years of age and females with Schizophrenia being the most common indications.